PROBLEMATIKA PENERAPAN PENDIDIKAN KARAKTER DI PONDOK PESANTREN KOTA PEKANBARU - Alfiah Alfiah (POTENSIA: Jurnal Kependidikan Islam, 2016)
The implementation of character building at Islamic Boarding School in Pekanbaru; Darel Hikmah Islamic Boarding School, Babussalam Islamic Boarding School, and Al-Kautsar Modern Islamic Boarding School is proceeded through 3 integrated ways, namely; through the subject courses, through local contents, and through students’ self development. Based on the preliminary study, writer found a discrepancy which indicates the implementation of character building in Islamic Boarding School Darel Hikmah, Babussalam and Al-Kautsar is not optimally applied. The discrepancy indicated that the character building in the schools does not have positive effect on students’ characters; to adore God Al mighty and all His creature; respectful and well-mannered, generous, mutual cooperation, self-confidence and hardworker, leadership and equitable, humble, tolerance, peaceful and unity. The application of character building at these schools has been investigated through 26 indicators. The research shows that the indicators are in good level; 73.16%. The first factor that support and barrier the application of character building in these Islamic Boarding Schools is funding; there is no specific fund to support the education character building implementation. The second is human resources; headmaster and teacher. Then, facilities and the last is teachers’ welfare.